Factores Predisponentes y Alternativas de Tratamiento de la Estomatitis Subprotésica. Revisión Sistemática (2023)
systematic research study was carried out to find out which is the predisposing factor with the highest prevalence of subprosthetic stomatitis and whether natural topical substances are effective and safe in comparison with conventional antifungals in the treatment of subprosthetic stomatitis in patients with total and removable prostheses. Objective. To identify the predisposing factors of subprosthetic stomatitis and treatment alternatives in patients with removable prostheses. Results. After applying the different selection criteria, the sample consisted of 43 articles in full text, where the main result showed the predisposing factors of sub-prosthetic stomatitis and treatment alternatives in patients with removable prostheses Conclusions. After the analysis it follows that the oral cavity is exposed to various factors and characteristics that favor or hinder the development of microorganisms and species such as Candida albicans considered the most causal of the Subprotésica Stomatitis, It was determined that the most frequent grade is type II and as for the management of this with drugs or alternative medicine, a greater use is observed with respect to new trends such as laserterapia Conclusions. After the analysis it follows that the oral cavity is exposed to various factors and characteristics that favor or hinder the development of microorganisms and species such as Candida albicans considered the most causal of the Subprotésica Stomatitis, It was determined that the most frequent grade is type II and as for the management of this with drugs or alternative medicine, a greater use is observed with respect to new trends such as laserterapia